Skip to content
New issue

Have a question about this project? # for a free GitHub account to open an issue and contact its maintainers and the community.

By clicking “#”, you agree to our terms of service and privacy statement. Weโ€™ll occasionally send you account related emails.

Already on GitHub? # to your account

[Bug] LaTeX from DeepSeek R1 causes frontend errors #5770

Closed
fred913 opened this issue Feb 5, 2025 · 5 comments ยท Fixed by #6063
Closed

[Bug] LaTeX from DeepSeek R1 causes frontend errors #5770

fred913 opened this issue Feb 5, 2025 · 5 comments ยท Fixed by #6063
Labels
๐Ÿ› Bug Something isn't working | ็ผบ้™ท released

Comments

@fred913
Copy link

fred913 commented Feb 5, 2025

๐Ÿ“ฆ Environment

Docker

๐Ÿ“Œ Version

v1.51.1

๐Ÿ’ป Operating System

Windows

๐ŸŒ Browser

Edge

๐Ÿ› Bug Description

When talking about a math problem it generates response, and then the error page shows.

Response text:

ๅฅฝ๏ผŒๆˆ‘็Žฐๅœจๅพ—่งฃๅ†ณ่ฟ™ไธชๅ…ณไบŽๆ•ฐๅˆ—็š„้—ฎ้ข˜ใ€‚้ข˜็›ฎ็ป™ๅฎšไบ†ไธ€ไธชๆญฃๅ‘ๆ•ฐๅˆ—{aโ‚™}๏ผŒ้ฆ–้กนaโ‚=4๏ผŒ้€’ๆŽจๅผๆ˜ฏaโ‚™ยฒ = a_{n+1} + 3n aโ‚™ -3ใ€‚ไปปๅŠกๅˆ†ๆˆไธค้ƒจๅˆ†๏ผŒ้ฆ–ๅ…ˆๆ˜ฏๆ นๆฎๅ‰ๅ‡ ้กนๆฑ‚ๅ‡บaโ‚‚ๅ’Œaโ‚ƒ๏ผŒๅ†ๆ นๆฎ่ฟ™ไธ‰้กน็š„่ง„ๅพ‹ๆฅ็Œœๅ‡บ้€š้กนๅ…ฌๅผ๏ผ›็ฌฌไบŒๅฐฑๆ˜ฏ็”จๆ•ฐๅญฆๅฝ’็บณๆณ•่ฏๆ˜Ž่ฟ™ไธช็Œœๆƒณๆญฃ็กฎ็š„ใ€‚่ฎฉๆˆ‘ไป”็ป†ๅˆ†ๆžไธ€ไธ‹๏ผŒไธ€ๆญฅๆญฅ่งฃๅ†ณ่ฟ™ไธช้—ฎ้ข˜ใ€‚

็ฌฌไธ€้ƒจๅˆ†๏ผŒๆฑ‚aโ‚‚ๅ’Œaโ‚ƒ๏ผŒ็„ถๅŽๅ†็Œœ้€š้กนๅ…ฌๅผใ€‚้ฆ–ๅ…ˆ๏ผŒๆˆ‘ๅบ”่ฏฅๆ นๆฎ้€’ๆŽจๅผๆฅ่ฎก็ฎ—aโ‚‚็š„ๅ€ผใ€‚ๆณจๆ„๏ผŒ่ฟ™้‡Œ็ป™ๅ‡บ็š„้€’ๆŽจๅผๆ˜ฏaโ‚™็š„ๅนณๆ–น็ญ‰ไบŽๅŽ้ข็š„้กนa_{n+1}ๅŠ 3nไน˜aโ‚™ๅ‡3ใ€‚้‚ฃไนˆ๏ผŒๅฏนไบŽn=1็š„ๆƒ…ๅ†ต๏ผŒๅณๅฝ“็”จaโ‚ๆฅ่ฎก็ฎ—aโ‚‚็š„ๆ—ถๅ€™๏ผŒๆˆ‘ไปฌๅฏไปฅไปฃๅ…ฅๅˆฐ้€’ๆŽจๅผไธญใ€‚่ฎฉn=1๏ผš

aโ‚็š„ๅนณๆ–น็ญ‰ไบŽaโ‚‚ๅŠ ไธŠ31aโ‚ๅ‡ๅŽป3ใ€‚็Žฐๅœจๅทฒ็Ÿฅaโ‚=4๏ผŒไปฃๅ…ฅ่ฟ›ๅŽป๏ผŒ4ยฒ = aโ‚‚ + 314 -3ใ€‚่ฎก็ฎ—ๅทฆ่พนๆ˜ฏ16๏ผŒๅณ่พนๆ˜ฏaโ‚‚ + 12 -3๏ผŒไนŸๅฐฑๆ˜ฏaโ‚‚ +9ใ€‚ๆ‰€ไปฅๆ–น็จ‹ๅฐฑๆ˜ฏ16 = aโ‚‚ +9๏ผŒ่งฃๅพ—aโ‚‚ = 16 -9 =7ใ€‚ๅฏนๅ—๏ผŸๅพ—ๆ ธๅฏนไธ€ไธ‹่ฟ็ฎ—ๆ˜ฏไธๆ˜ฏๅ“ช้‡Œ้”™ไบ†ใ€‚

็ป“ๆžœๆ˜ฏaโ‚‚=7๏ผŒๅ› ไธบ1)ๅธฆๅ…ฅn=1๏ผŒๅผๅญๅ˜ๆˆ aโ‚ยฒ =aโ‚‚ +31aโ‚ -3 โ†’4ยฒ= aโ‚‚ +3*4 -3 โ†’16= aโ‚‚ +12 -3 โ†’16=aโ‚‚+9 โ†’aโ‚‚=7ใ€‚ๅฏนๅง๏ผŸ

ๆŽฅไธ‹ๆฅๆฑ‚aโ‚ƒ็š„่ฏ๏ผŒ้œ€่ฆไฝฟ็”จaโ‚‚็š„่กจ่พพๅผ๏ผŒ็„ถๅŽๅธฆๅ…ฅn=2ๆ—ถ็š„้€’ๆŽจๅผ๏ผŒๅŒๆ ท็š„ๆ–นๅผ่งฃๅ‡บaโ‚ƒใ€‚่ฟ™ๆ—ถๅ€™ๅผๅญๅบ”ๆ˜ฏaโ‚‚ยฒ =aโ‚ƒ +32aโ‚‚ -3๏ผŒๆ นๆฎๅทฒ็Ÿฅ๏ผŒaโ‚‚=7๏ผŒๅˆ™ๅธฆๅ…ฅๅพ—๏ผš7ยฒ = aโ‚ƒ +327 -3 โ†’49= aโ‚ƒ +42 -3 โ†’ไนŸๅฐฑๆ˜ฏ49 =aโ‚ƒ +39 โ†’่งฃๅพ—aโ‚ƒ=49-39=10ใ€‚ๆ‰€ไปฅaโ‚ƒ=10ใ€‚

็Žฐๅœจๅ‰ไธ‰ไธช้กนๆ˜ฏaโ‚=4๏ผŒaโ‚‚=7๏ผŒaโ‚ƒ=10ใ€‚็Žฐๅœจ่ฆ็œ‹่ฟ™ไธ‰ไธชๆ•ฐ็š„่ง„ๅพ‹๏ผŒ็Œœๆƒณ้€š้กนๅ…ฌๅผใ€‚ไป–ไปฌไน‹้—ดๅฏ่ƒฝ้š่—็š„่ง„ๅพ‹ๅฏ่ƒฝๆ˜ฏ็บฟๆ€ง็š„๏ผŸๅณ็›ธ้‚ปไธค้กน็š„ๅทฎ๏ผŒไพ‹ๅฆ‚7-4=3๏ผŒ10-7=3๏ผŒ่ฟ™ๆ ทไธ‹ไธ€ไธชๅฏ่ƒฝๆ˜ฏaโ‚„=13๏ผŸๆˆ–่€…ๆ˜ฏๅฆๅญ˜ๅœจๆŸ็งๆ•ฐๅˆ—็ฑปๅž‹ใ€‚

ไธ่ฟ‡ๆ นๆฎ้ข˜็›ฎ็ป™ๅ‡บ็š„้€’ๆŽจๅผๆฏ”่พƒ็‰นๅˆซ๏ผŒไธๆ˜ฏ็บฟๆ€ง็š„้€’ๅฝ’๏ผŒ่€Œๆ˜ฏๅธฆๆœ‰ๅนณๆ–น้กน็š„๏ผŒๆ˜ฏๅฆๅฏ่ƒฝ้€š้กนๅ…ฌๅผไธบไธ€ๆฌกๅ‡ฝๆ•ฐๅฝขๅผ๏ผŒไพ‹ๅฆ‚ aโ‚™ = 3n +1๏ผŸ

็œ‹ไธ€ไธ‹ๆ˜ฏๅฆๆ˜ฏ่ฟ™็งๅฏ่ƒฝ็š„๏ผŒๆฏ”ๅฆ‚ๅฝ“n=1ๆ—ถ๏ผŒ31+1=4๏ผŒ็กฎๅฎž็ฌฆๅˆaโ‚=4๏ผ›ๅฝ“n=2ๆ—ถ๏ผŒ32+1=7๏ผŒ็ฌฆๅˆaโ‚‚=7๏ผ›ๅฝ“n=3ๆ—ถ๏ผŒ3*3+1=10๏ผŒไนŸ็ฌฆๅˆaโ‚ƒ=10ใ€‚็œ‹่ตทๆฅๅƒๆ˜ฏaโ‚™=3n +1๏ผŒ้‚ฃไนˆ่ฟ™ไธช็ŒœๆƒณไผผไนŽๅˆ็†๏ผŸๆˆ–่ฎธๅ‘ข๏ผŸ

ๅฅฝ็š„๏ผŒๆŽฅไธ‹ๆฅๆ˜ฏ่ฏๆ˜Ž้ƒจๅˆ†๏ผŒ้œ€่ฆ็”จๆ•ฐๅญฆๅฝ’็บณๆณ•ๆฅ่ฏๆ˜Ž่ฟ™ไธช็Œœๆƒณใ€‚

้ฆ–ๅ…ˆ๏ผŒๆ•ฐๅญฆๅฝ’็บณๆณ•้œ€่ฆไธคๆญฅ๏ผšๅŸบ็ก€ๆญฅ้ชคๅ’Œๅฝ’็บณๆญฅ้ชคใ€‚ๅŸบ็ก€ๆญฅ้ชค่ฆ่ฏๆ˜Žๅฝ“n=1ๆ—ถๅ‘ฝ้ข˜ๆˆ็ซ‹๏ผŒๅณaโ‚=4=3*1+1=4๏ผŒๆˆ็ซ‹ใ€‚่ฟ™ๆ˜ฏๆญฃ็กฎ็š„ใ€‚

้‚ฃไนˆๅฝ’็บณๅ‡่ฎพ่ฎพไธบๅฝ“n=kๆ—ถ๏ผŒa_k=3k+1๏ผŒ่ฟ™ๅ‡่ฎพๆˆ็ซ‹๏ผŒ่ฟ›่€Œ้œ€่ฆ่ฏๆ˜Žn=k+1ๆ—ถa_{k+1}=3(k+1)+1=3k+4ๆ˜ฏๅฆๆˆ็ซ‹ใ€‚

็„ถ่€Œ่ฆๆณจๆ„ๅŽŸ้ข˜ไฝฟ็”จ็š„ๆ˜ฏ้€’ๆŽจๅผa_nยฒ = a_{n+1} + 3n a_n -3๏ผŒๅ…ถไธญๅŽŸๅผไธญn็š„่Œƒๅ›ดไปŽ1ๅผ€ๅง‹ๅˆฐๆ‰€ๆœ‰่‡ช็„ถๆ•ฐใ€‚ๆ‰€ไปฅ๏ผŒๅบ”้‡‡็”จๅฝ’็บณๆŽจๅฏผๅ‡บๅฝ“ๅ‡่ฎพa_k=3k+1ๆˆ็ซ‹ๆ—ถ๏ผŒ่ฏๆ˜Ža_{k+1}=3(k+1)+1=3k+4.

่ฟ™ไธช่ฟ‡็จ‹ๅฏ่ƒฝ้œ€่ฆๅฐ†ๅฝ’็บณๅ‡่ฎพไปฃๅ…ฅ้€’ๆŽจๅผ่ฟ›่กŒ่ฎก็ฎ—ใ€‚

ไฝ†ๆ˜ฏ้œ€่ฆๆณจๆ„่ฟ™ไธ€็‚นไธไธ€ๅฎš็›ดๆŽฅๅฏ่กŒ๏ผŒๅ› ไธบๅฏนไบŽ็ป™ๅฎš็š„้€’ๆŽจๅผ๏ผŒๅฏ่ƒฝ้œ€่ฆไปŽnๅˆฐn+1ๆ—ถ็š„ไพ่ต–ๅ…ณ็ณปๆฅๅฏผๅ‡บๅŽ็š„้กนๆ˜ฏๅฆ็ฌฆๅˆใ€‚่ฟ™ไธช่ฟ‡็จ‹้œ€่ฆ่ฏฆ็ป†ๆŽจๅฏผๆ˜ฏๅฆๆญฃ็กฎใ€‚ๆˆ–่€…่ฏด๏ผš ๅ‡่ฎพๅฏนไบŽไปปๆ„็š„n=k๏ผŒa_k=3k+1๏ผŒ้‚ฃไนˆ้€’ๆŽจๅผa_kยฒ =a_{k+1} +3k*a_k -3้‡Œ้ข็š„a_{k+1}ไผš็ญ‰ไบŽไป€ไนˆๅ‘ข๏ผŸ

ๅธฆๅ…ฅa_k=3k+1๏ผŒๅทฆ่พนa_kยฒ=(3k+1)^2=9kยฒ +6k +1๏ผ›ๅณ่พนๅˆ™ๆ˜ฏa_{k+1} +3k*(3k+1) -3.

ๆ นๆฎ็ญ‰ๅผ๏ผš9kยฒ+6k+1 = a_{k+1} +3k*(3k+1) -3.

ๅณ่พน็š„่ฎก็ฎ—: 3k*(3k+1)ๆ˜ฏ9kยฒ +3k๏ผŒๆ•ดไธชๅณ่พน็š„่กจ่พพๅผไธบ a_{k+1} +9kยฒ +3k -3ใ€‚ๆญคๆ—ถๅทฆ่พน็ญ‰ไบŽๅณ่พน๏ผŒๆ‰€ไปฅๆ–น็จ‹ๆ˜ฏ๏ผš9kยฒ +6k +1 = a_{k+1} +9kยฒ +3k -3.

็ฎ€ๅŒ–็š„่ฏ๏ผŒๅฏไปฅๅ…ˆๅฏนไธค่พน็บฆๅŽป็›ธๅŒ็š„้กนใ€‚ๅทฆ่พน็š„9kยฒ=ๅณ่พน็š„9kยฒ๏ผŒๅ‰ฉไธ‹็š„ๅทฆ่พนๆ˜ฏ6k +1๏ผŒๅณ่พนๅฏนๅ‰ฉไธ‹็š„้กนๆ˜ฏ a_{k+1} +3k -3ใ€‚

่ฟ™ๆ ทๅฐฑๅพ—็ญ‰ๅผ๏ผš6k +1 = a_{k+1} +3k -3.

ๆŠŠๅทฆ่พน็š„6k +1 ๅ˜ๆˆๅณ่พน็š„่ฏ๏ผŒๅˆ™a_{k+1} +3k -3=6k +1 โ†’่งฃ๏ผŒ็งป้กนๅพ—a_{k+1}=6k +1 -3k +3=3k +4ใ€‚ๅ› ๆญค๏ผŒ่ฟ™ไธช่ฟ‡็จ‹ๅฏนๅ—๏ผŸ

่ฟ™ๆ ทๅฏไปฅๅพ—ๅ‡บ a_{k+1}=3k+4=3(k+1)+1๏ผŒๅณ็กฎๅฎžๆปก่ถณ a_{k+1}=3(k+1)+1ใ€‚่ฟ™่ฏดๆ˜Žๅฆ‚ๆžœn=kๆ—ถ๏ผŒa_k=3k+1ๆˆ็ซ‹๏ผŒๅˆ™n=k+1ๆ—ถ๏ผŒa_{k+1}=3(k+1)+1ๆˆ็ซ‹ใ€‚่ฟ™่ฏดๆ˜Ž้€š่ฟ‡ๆ•ฐๅญฆๅฝ’็บณๆณ•๏ผŒๅฏนไบŽๆ‰€ๆœ‰่‡ช็„ถๆ•ฐnโ‰ฅ1๏ผŒ่ฏฅๅ…ฌๅผๆˆ็ซ‹ใ€‚

้‚ฃ็œ‹ๆฅ่ฟ™ไธช็Œœๆƒณๆ˜ฏๅฏน็š„๏ผŒๆ‰€ไปฅ้—ฎ้ข˜ๅพ—ไปฅ่งฃๅ†ณใ€‚

ไฝ†ๆœ‰ไธ€ไธ้—ฎ้ข˜๏ผšๆ˜ฏๅฆๆœ‰ๅฏ่ƒฝๅ‰ๅ‡ ้กน็ฌฆๅˆๆŸไธช่ง„ๅพ‹ไฝ†ๅŽ้ขไธ็ฌฆ๏ผŒ่ฟ™้ข˜่ฎพ็ฝฎๆ˜พ็„ถๆ˜ฏ้€š่ฟ‡้€’ๆŽจๅผ็ป™ๅ‡บ็š„๏ผŒไธ”ๆ›ฟๆขๆญฃ็กฎ็š„ๆƒ…ๅ†ตไธ‹๏ผŒ่ฟ™้‡Œๅฝ’็บณๆณ•ๆ˜ฏๅบ”็”จๆญฃ็กฎ็š„๏ผŸๆ˜ฏ็š„๏ผŒๅ› ไธบๅœจ้€’ๆŽจๅผไน‹ไธ‹๏ผŒๆฏไธช้กน้ƒฝไพ่ต–ๅ‰ไธ€้กน๏ผŒๅ› ๆญคๆ•ฐๅญฆๅฝ’็บณๆณ•้€‚ๅˆ่ฟ™็งๆƒ…ๅ†ตใ€‚

ๆ€ปไน‹๏ผŒ็ฌฌไธ€ๆญฅๆฑ‚ๅ‡บaโ‚‚=7ๅ’Œaโ‚ƒ=10๏ผŒๅ‰ไธ‰้กนๅ‘ˆ็Žฐๅ‡บ็บฟๆ€ง่ง„ๅพ‹๏ผšaโ‚™=3n+1ใ€‚้€š่ฟ‡ๆ•ฐๅญฆๅฝ’็บณๆณ•้ชŒ่ฏ๏ผŒๅฝ“ๅ‡่ฎพn=kๆˆ็ซ‹ๆ—ถ๏ผŒn=k+1ไนŸๆˆ็ซ‹๏ผŒๆ‰€ไปฅๆ•ดไธช้€š้กนๅ…ฌๅผๆˆ็ซ‹ใ€‚

็Žฐๅœจ้œ€่ฆ็ณป็ปŸๅŒ–ๅœฐๆŠŠ่ฟ™ไธช่ฟ‡็จ‹ๆ•ด็†ไธ‹ๆฅใ€‚

็ญ”ๆกˆ

  1. ไปฃๅ…ฅ้€’ๆŽจๅผๆฑ‚ๅพ—aโ‚‚=7๏ผŒaโ‚ƒ=10ใ€‚็Œœๆƒณ้€š้กนๅ…ฌๅผไธบ$\boxed{a_n = 3n + 1}$ใ€‚

  2. ๆ•ฐๅญฆๅฝ’็บณๆณ•่ฏๆ˜Ž่ฟ‡็จ‹ๅฆ‚ไธ‹๏ผš

    • ๅŸบไพ‹๏ผšๅฝ“n=1ๆ—ถ๏ผŒaโ‚=4=3ร—1+1๏ผŒๆˆ็ซ‹ใ€‚
    • ๅ‡่ฎพ๏ผšๅฝ“n=kๆ—ถ๏ผŒa_k=3k+1ๆˆ็ซ‹ใ€‚
    • ้€’ๆŽจ๏ผšๅฐ†a_kไปฃๅ…ฅ้€’ๆŽจๅผๅพ—๏ผš
      [
      (3k+1)^2 = a_{k+1} + 3k(3k+1) - 3
      ]
      ่ฎก็ฎ—ๅพ—a_{k+1}=3(k+1)+1๏ผŒๅณ้€š้กนๅ…ฌๅผๅฏนn=k+1ๆˆ็ซ‹ใ€‚
    • ็ป“่ฎบ๏ผš็Œœๆƒณๆˆ็ซ‹๏ผŒ้€š้กนๅ…ฌๅผไธบ$\boxed{a_n = 3n + 1}$ใ€‚

็Ÿฅ่ฏ†็‚นๅ›ž้กพ

  1. ้€’ๆŽจๆ•ฐๅˆ—ๆฑ‚่งฃ๏ผš้€š่ฟ‡็ป™ๅฎš็š„้€’ๆŽจๅ…ณ็ณปๅผไพๆฌก่ฎก็ฎ—ๆ•ฐๅˆ—็š„้กนใ€‚
  2. ๆ•ฐๅญฆๅฝ’็บณๆณ•๏ผšไธ€็ง่ฏๆ˜Žๆ–นๆณ•๏ผŒ็”จไบŽ้ชŒ่ฏๆŸๅ‘ฝ้ข˜ๅฏนๆ‰€ๆœ‰่‡ช็„ถๆ•ฐๆˆ็ซ‹ใ€‚

่ฏฆ็ป†่งฃ้ข˜ๆญฅ้ชค

้—ฎ้ข˜1๏ผšๆฑ‚ ( a_2 )ใ€( a_3 ) ๅนถ็Œœๆƒณ้€š้กนๅ…ฌๅผ

  1. ่ฎก็ฎ— ( a_2 )
    ๆ นๆฎ้€’ๆŽจๅผ ( a_n^2 = a_{n+1} + 3n a_n - 3 )๏ผŒๅฝ“ ( n=1 ) ๆ—ถ๏ผš
    [
    a_1^2 = a_2 + 3 \cdot 1 \cdot a_1 - 3
    ]
    ๅทฒ็Ÿฅ ( a_1 = 4 )๏ผŒไปฃๅ…ฅ๏ผš
    [
    4^2 = a_2 + 3 \cdot 1 \cdot 4 - 3 \implies 16 = a_2 + 9 \implies a_2 = 7
    ]

  2. ่ฎก็ฎ— ( a_3 )
    ๅฝ“ ( n=2 ) ๆ—ถ๏ผŒไปฃๅ…ฅ้€’ๆŽจๅผ๏ผš
    [
    a_2^2 = a_3 + 3 \cdot 2 \cdot a_2 - 3
    ]
    ๅทฒ็Ÿฅ ( a_2 = 7 )๏ผŒไปฃๅ…ฅ๏ผš
    [
    7^2 = a_3 + 42 - 3 \implies 49 = a_3 + 39 \implies a_3 = 10
    ]

  3. ็Œœๆƒณ้€š้กนๅ…ฌๅผ
    ่ง‚ๅฏŸๅ‰ไธ‰้กน๏ผš( a_1 = 4 )๏ผŒ( a_2 = 7 )๏ผŒ( a_3 = 10 )๏ผŒๅฏ่ง ( a_n ) ๆ˜ฏ็บฟๆ€ง้€’ๅขž็š„๏ผŒ้ฆ–ๆฌกๅทฎไธบ ( 3 )ใ€‚ๅ› ๆญค็Œœๆƒณ้€š้กนๅ…ฌๅผไธบ๏ผš
    [
    a_n = 3n + 1
    ]


้—ฎ้ข˜2๏ผš็”จๆ•ฐๅญฆๅฝ’็บณๆณ•่ฏๆ˜Ž็Œœๆƒณ

  1. ๅŸบไพ‹้ชŒ่ฏ (n=1)
    ๅฝ“ ( n=1 ) ๆ—ถ๏ผŒ( a_1 = 3 \cdot 1 + 1 = 4 )๏ผŒไธŽๅทฒ็Ÿฅ็›ธ็ฌฆใ€‚

  2. ๅฝ’็บณๅ‡่ฎพ
    ๅ‡่ฎพๅฝ“ ( n = k ) ๆ—ถ๏ผŒ( a_k = 3k + 1 ) ๆˆ็ซ‹ใ€‚

  3. ๅฝ’็บณๆญฅ้ชค (่ฏๆ˜Ž ( n = k+1 ))
    ๆ นๆฎ้€’ๆŽจๅผ๏ผŒๅฐ† ( a_k = 3k + 1 ) ไปฃๅ…ฅ๏ผš
    [
    (3k + 1)^2 = a_{k+1} + 3k(3k + 1) - 3
    ]
    ๅฑ•ๅผ€ๅนถๅŒ–็ฎ€ๅทฆ่พน๏ผš
    [
    9k^2 + 6k + 1 = a_{k+1} + 9k^2 + 3k - 3
    ]
    ๆถˆๅŽป ( 9k^2 )๏ผŒๅนถๆ•ด็†๏ผš
    [
    6k + 1 = a_{k+1} + 3k - 3 \implies a_{k+1} = 3k + 4
    ]
    ่ฟ™ๆญฃๆ˜ฏ ( n = k+1 ) ๆ—ถ็š„็Œœๆƒณ้€š้กน๏ผš
    [
    a_{k+1} = 3(k + 1) + 1
    ]

  4. ็ป“่ฎบ
    ็”ฑๆ•ฐๅญฆๅฝ’็บณๆณ•ๅฏ็Ÿฅ๏ผŒ้€š้กนๅ…ฌๅผๅฏนๆ‰€ๆœ‰่‡ช็„ถๆ•ฐ ( n ) ๆˆ็ซ‹ใ€‚


ๆœ€็ปˆ็ญ”ๆกˆ

  1. ่ฎก็ฎ—็ป“ๆžœไธŽ็Œœๆƒณ๏ผš
    [
    a_2 = 7,\quad a_3 = 10,\quad \boxed{a_n = 3n + 1}
    ]

  2. ๆ•ฐๅญฆๅฝ’็บณๆณ•้ชŒ่ฏๆˆๅŠŸ๏ผš
    [
    \boxed{a_n = 3n + 1}
    ]

๐Ÿ“ท Recurrence Steps

Send the math problem.

่ฎพๆญฃๅ‘ๆ•ฐๅˆ— $ { a_n } $ ็š„้ฆ–้กนไธบ $ 4 $ ๏ผŒๆปก่ถณ $ a^2_n = a_{n+1} + 3na_n - 3 $.

  1. ๆฑ‚ $ a_2 $ ๅ’Œ $ a_3 $๏ผŒๆ นๆฎๅ‰ไธ‰้กน็š„่ง„ๅพ‹็Œœๆƒณ่ฏฅๆ•ฐๅˆ—็š„้€š้กนๅ…ฌๅผ
  2. ็”จๆ•ฐๅญฆๅฝ’็บณๆณ•่ฏๆ˜Žไฝ ็š„็Œœๆƒณใ€‚

๐Ÿšฆ Expected Behavior

Correctly display the solution of the math problem

๐Ÿ“ Additional Information

Frontend logs are uploaded on PasteBin

@fred913 fred913 added the ๐Ÿ› Bug Something isn't working | ็ผบ้™ท label Feb 5, 2025
@github-project-automation github-project-automation bot moved this to Roadmap - Chat 1.x in Lobe Chat Routine Feb 5, 2025
@lobehubbot
Copy link
Member

๐Ÿ‘€ @fred913

Thank you for raising an issue. We will investigate into the matter and get back to you as soon as possible.
Please make sure you have given us as much context as possible.
้žๅธธๆ„Ÿ่ฐขๆ‚จๆไบค issueใ€‚ๆˆ‘ไปฌไผšๅฐฝๅฟซ่ฐƒๆŸฅๆญคไบ‹๏ผŒๅนถๅฐฝๅฟซๅ›žๅคๆ‚จใ€‚ ่ฏท็กฎไฟๆ‚จๅทฒ็ปๆไพ›ไบ†ๅฐฝๅฏ่ƒฝๅคš็š„่ƒŒๆ™ฏไฟกๆฏใ€‚

@lobehubbot
Copy link
Member

Bot detected the issue body's language is not English, translate it automatically. ๐Ÿ‘ฏ๐Ÿ‘ญ๐Ÿป๐Ÿง‘โ€๐Ÿคโ€๐Ÿง‘๐Ÿ‘ซ๐Ÿง‘๐Ÿฟโ€๐Ÿคโ€๐Ÿง‘๐Ÿป๐Ÿ‘ฉ๐Ÿพโ€๐Ÿคโ€๐Ÿ‘จ๐Ÿฟ๐Ÿ‘ฌ๐Ÿฟ


๐Ÿ“ฆ Environment

Docker

๐Ÿ“Œ Version

v1.51.1

๐Ÿ’ป Operating System

Windows

๐ŸŒ Browser

Edge

๐Ÿ› Bug Description

When talking about a math problem it generates response, and then the error page shows.

Response text:

"

OK, I have to solve this problem with the sequence now. The question gives a forward sequence {aโ‚™}, the first term aโ‚=4, and the recursive formula is aโ‚™ยฒ = a_{n+1} + 3n aโ‚™ -3. The task is divided into two parts. First, we calculate aโ‚‚ and aโ‚ƒ based on the first few terms, and then guess the general formula based on the rules of these three terms; the second is to use mathematical induction to prove that this conjecture is correct. Let me analyze it carefully and solve this problem step by step.
"
Part 1, find aโ‚‚ and aโ‚ƒ, and then guess the term formula. First, I should calculate the value of aโ‚‚ based on the recursive formula. Note that the recursive formula given here is that the square of aโ‚™ is equal to the following term a_{n+1} plus 3n times aโ‚™ to minus 3. Then, for the case where n=1, that is, when aโ‚ is used to calculate aโ‚‚, we can substitute it into the recursive formula. Let n=1:
"
The square of aโ‚ is equal to aโ‚‚ plus 31aโ‚ minus 3. Now it is known that aโ‚=4, substitute it, 4ยฒ = aโ‚‚ + 314 -3. Calculate that the left is 16 and the right is aโ‚‚ + 12 -3, that is, aโ‚‚ +9. So the equation is 16 = aโ‚‚ +9, and the solution is aโ‚‚ = 16 -9 =7. Is it right? You have to check if the operation is wrong.
"
The result is aโ‚‚=7, because 1) brings n=1, and the formula becomes aโ‚ยฒ =aโ‚‚ +31aโ‚ -3 โ†’4ยฒ= aโ‚‚ +34 -3 โ†’16= aโ‚‚ +12 -3 โ†’ 16=aโ‚‚+9 โ†’aโ‚‚=7. Right?
"
Next, if you want aโ‚ƒ, you need to use the expression of aโ‚‚, and then bring the recursive formula when n=2, and solve aโ‚ƒ in the same way. At this time, the formula should be aโ‚‚ยฒ =aโ‚ƒ +3
2aโ‚‚ -3. According to the known, aโ‚‚=7, it will bring it into: 7ยฒ = aโ‚ƒ +327 -3 โ†’49= aโ‚ƒ +42 -3 โ†’ That is, 49 = aโ‚ƒ +39 โ†’The solution is to aโ‚ƒ=49-39=10. So aโ‚ƒ=10.
"
Now the first three terms are aโ‚=4, aโ‚‚=7, aโ‚ƒ=10. Now we need to look at the rules of these three numbers and guess the general formula. The law that might be hidden between them may be linear? That is, the difference between two adjacent terms, such as 7-4=3, 10-7=3, so the next one may be aโ‚„=13? Or whether there is some sort of sequence type.
"
However, the recursion formula given according to the question is more special. It is not linear recursion, but with square terms. Is it possible that the general term formula is a one-time function form, such as aโ‚™ = 3n +1?
"
Check whether this is possible. For example, when n=1, 3
1+1=4, it does meet aโ‚=4; when n=2, 32+1=7, it meets aโ‚‚=7; When n=3, 33+1=10 also meets aโ‚ƒ=10. It looks like aโ‚™=3n +1, so this conjecture seems reasonable? Maybe?
"
OK, next is the proof part, which needs to be proved by mathematical induction.
"
First, mathematical induction requires two steps: basic steps and induction steps. The basic steps should prove that when n=1 the proposition is true, that is, aโ‚=4=31+1=4, which is true. that's right.
"
Then the induction assumption is set to when n=k, a_k=3k+1, which is true, and it is necessary to prove that when n=k+1 a_{k+1}=3(k+1)+1=3k+4 Whether it is true.
"
However, it should be noted that the original question uses the recursive formula a_nยฒ = a_{n+1} + 3n a_n -3, where the range of n in the original formula starts from 1 to all natural numbers. Therefore, induction should be used to deduce that when the assumption a_k=3k+1 is true, prove that a_{k+1}=3(k+1)+1=3k+4.
"
This process may require the inductive assumption to be substituted into recursive formulas for calculation.
"
However, it is important to note that this is not necessarily feasible, because for a given recursive formula, the dependency from n to n+1 may be required to derive the following terms. This process requires detailed deduction whether it is correct. Or: Assume that for any n=k, a_k=3k+1, then what will the a_{k+1} in the recursive formula a_kยฒ =a_{k+1} +3k
a_k -3 equal?
"
Bring in a_k=3k+1, on the left a_kยฒ=(3k+1)^2=9kยฒ +6k +1; on the right a_{k+1} +3k*(3k+1) -3.
"
According to the equation: 9kยฒ+6k+1 = a_{k+1} +3k*(3k+1) -3.
"
Calculation on the right: 3k*(3k+1) is 9kยฒ +3k, and the expression on the whole right is a_{k+1} +9kยฒ +3k -3. At this time, the left side is equal to the right side, so the equation is: 9kยฒ +6k +1 = a_{k+1} +9kยฒ +3k -3.
"
To simplify, you can first make the same items on both sides. The left 9kยฒ = the right 9kยฒ, the left left is 6k +1, and the left term on the right is a_{k+1} +3k -3.
"
This gives the equation: 6k +1 = a_{k+1} +3k -3.
"
If the 6k on the left +1 is turned into the right, then a_{k+1} +3k -3=6k +1 โ†’ Solution, and the term is moved to a_{k+1}=6k +1 -3k +3=3k + 4. So, is this process right?
"
This results in a_{k+1}=3k+4=3(k+1)+1, that is, a_{k+1}=3(k+1)+1 is indeed satisfied. This means that if a_k=3k+1 is true when n=k+1 is true when a_{k+1}=3(k+1)+1 is true. This shows that through mathematical induction, this formula holds true for all natural numbers nโ‰ฅ1.
"
It seems that this conjecture is correct, so the problem is solved.
"
But there is a little problem: is it possible that the first few items meet a certain rule but the latter does not meet? This question is obviously given through recursive form, and the replacement is correct. Is the induction here the correct application? Yes, because under recursive, each term depends on the previous one, so mathematical induction is suitable for this situation.
"
In short, the first step is to find aโ‚‚=7 and aโ‚ƒ=10. The first three terms show a linear law: aโ‚™=3n+1. Through mathematical induction verification, when the assumption that n=k is true, n=k+1 is also true, so the entire general formula is true.
"
Now we need to systematically sort out this process.
"
"
Answer
"

  1. Substitute the recursive formula to find aโ‚‚=7, aโ‚ƒ=10. The conjecture formula is $\boxed{a_n = 3n + 1}$.
    "
  2. The mathematical induction proof process is as follows:
  • Basic Example: When n=1, aโ‚=4=3ร—1+1, which is true.
  • Suppose: When n=k, a_k=3k+1 holds.
  • Recursive: Substitute a_k into the recursive form to get:
    [
    (3k+1)^2 = a_{k+1} + 3k(3k+1) - 3
    ]
    Calculate a_{k+1}=3(k+1)+1, that is, the general formula is valid for n=k+1.
  • Conclusion: The conjecture is true, and the general formula is $\boxed{a_n = 3n + 1}$.

"

Review of knowledge points

"

  1. Recursive sequence solution: Calculate the terms of the sequence in sequence through the given recursive relationship.
  2. Mathematical Induction: A proof method used to verify that a proposition holds for all natural numbers.
    "

"

Detailed solution steps

"

Question 1: Find ( a_2 ), ( a_3 ) and guess the general term formula

"

  1. Calculation ( a_2 )
    According to the recursive expression ( a_n^2 = a_{n+1} + 3n a_n - 3 ), when ( n=1 ):
    [
    a_1^2 = a_2 + 3 \cdot 1 \cdot a_1 - 3
    ]
    Known ( a_1 = 4 ), substitute:
    [
    4^2 = a_2 + 3 \cdot 1 \cdot 4 - 3 \implies 16 = a_2 + 9 \implies a_2 = 7
    ]
    "
  2. Calculation ( a_3 )
    When ( n=2 ), substitute for recursive expression:
    [
    a_2^2 = a_3 + 3 \cdot 2 \cdot a_2 - 3
    ]
    Known ( a_2 = 7 ), substitute:
    [
    7^2 = a_3 + 42 - 3 \implies 49 = a_3 + 39 \implies a_3 = 10
    ]
    "
  3. Conjecture formula
    Observe the first three terms: ( a_1 = 4 ), ( a_2 = 7 ), ( a_3 = 10 ), it can be seen that ( a_n ) is linearly incremented, and the first difference is ( 3 ). Therefore, the conjecture formula is:
    [
    a_n = 3n + 1
    ]
    "

"

Question 2: Prove conjectures using mathematical induction

"

  1. Basic Example Verification (n=1)
    When ( n=1 ), ( a_1 = 3 \cdot 1 + 1 = 4 ), which matches the known.
    "
  2. Inductive Hypothesis
    Assume that when ( n = k ), ( a_k = 3k + 1 ) holds.
    "
  3. Induction steps (Prove ( n = k+1 ))
    According to the recursive formula, substitute ( a_k = 3k + 1 ) into:
    [
    (3k + 1)^2 = a_{k+1} + 3k(3k + 1) - 3
    ]
    Expand and simplify the left:
    [
    9k^2 + 6k + 1 = a_{k+1} + 9k^2 + 3k - 3
    ]
    Eliminate ( 9k^2 ) and organize:
    [
    6k + 1 = a_{k+1} + 3k - 3 \implies a_{k+1} = 3k + 4
    ]
    This is exactly the conjecture term when ( n = k+1 ):
    [
    a_{k+1} = 3(k+1) + 1
    ]
    "
  4. Conclusion
    From mathematical induction, we can see that the general term formula holds for all natural numbers ( n ).
    "

"

Final answer

"

  1. ** Calculation results and conjectures**:
    [
    a_2 = 7,\quad a_3 = 10,\quad \boxed{a_n = 3n + 1}
    ]
    "
  2. Mathematical induction verification was successful:
    [
    \boxed{a_n = 3n + 1}
    ]

๐Ÿ“ท Recurrence Steps

Send the math problem.

Suppose the first term of the forward sequence $ { a_n } $ is $ 4 $ , satisfying $ a^2_n = a_{n+1} + 3na_n - 3 $.
"

  1. Find $ a_2 $ and $ a_3 $, and guess the general formula of the sequence according to the law of the first three terms
  2. Prove your conjecture using mathematical induction.

๐Ÿšฆ Expected Behavior

NO Response

๐Ÿ“ Additional Information

Frontend logs are uploaded on PasteBin

@fred913
Copy link
Author

fred913 commented Feb 5, 2025

Updated the issue body but the bot doesn't update translations; Except Behabior is 'Correctly show the solution to the math problem'

@lobehubbot
Copy link
Member

โœ… @fred913

This issue is closed, If you have any questions, you can comment and reply.
ๆญค้—ฎ้ข˜ๅทฒ็ปๅ…ณ้—ญใ€‚ๅฆ‚ๆžœๆ‚จๆœ‰ไปปไฝ•้—ฎ้ข˜๏ผŒๅฏไปฅ็•™่จ€ๅนถๅ›žๅคใ€‚

@lobehubbot
Copy link
Member

๐ŸŽ‰ This issue has been resolved in version 1.53.5 ๐ŸŽ‰

The release is available on:

Your semantic-release bot ๐Ÿ“ฆ๐Ÿš€

# for free to join this conversation on GitHub. Already have an account? # to comment
Labels
๐Ÿ› Bug Something isn't working | ็ผบ้™ท released
Projects
Status: Done
Development

Successfully merging a pull request may close this issue.

2 participants